Congenital thrombocytopenia in a neonate with an interstitial microdeletion of 3q26.2q26.31. Issue 2 (10th November 2015) - Bouman, Arjan; Knegt, Lia; Gröschel, Stefan; Erpelinck, Claudia; Sanders, Mathijs; Delwel, Ruud; Kuijpers, Taco; Cobben, Jan Maarten
Abstract : Interstitial deletions encompassing the 3q26.2 region are rare. Only one case‐report was published this far describing a patient with an interstitial deletion of 3q26.2 (involving the MDS1‐EVI1 complex ( MECOM )) and congenital thrombocytopenia. In this report we describe a case of a neonate with congenital thrombocytopenia and a constitutional 4.52 Mb deletion of 3q26.2q26.31 including TERC and the first 2 exons of MECOM, involving MDS1 but not EVI1 . The deletion was demonstrated by array‐CGH on lymphocytes. Our report confirms that congenital thrombocytopenia can be due to a constitutional deletion of 3q26.2 involving MECOM . We suggest that in case of unexplained neonatal thrombocytopenia, with even just slight facial dysmorphism, DNA microarray on peripheral blood should be considered early in the diagnostic work‐up. © 2015 Wiley Periodicals, Inc.